Spin-Off Implementation of Sharia Business Units in Indonesian General Insurance Companies: Regulatory, Managerial, and Financial Perspectives - Eko Suryawadi; Hendra Candra; Abdul Rahman (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study aims to analyze the implementation of the spin-off of Sharia Business Units (Unit Usaha Syariah/UUS) in general insurance companies in Indonesia from regulatory, managerial, and financial perspectives. The study is motivated by the mandatory separation policy stipulated in Law No. 4 of 2023 concerning Financial Sector Development and Strengthening and Financial Services Authority Regulation (POJK) No. 11 of 2023, which aim to strengthen the institutional structure and competitiveness of the Islamic financial industry. This study employs a descriptive qualitative approach using secondary data derived from regulations, academic literature, industry reports, financial statements, and official publications issued by the Financial Services Authority and related institutions. The analytical framework combines normative and empirical approaches to examine the implementation dynamics of the spin-off policy. The findings indicate that, from a regulatory perspective, the implementation process involves minimum capital fulfillment, portfolio transfer, regulatory approval, and the establishment of independent sharia entities. From a managerial perspective, the spin-off requires organizational restructuring, strengthening of sharia-based human resources, separation of operational systems, and implementation of sharia-based good corporate governance. From a financial perspective, the spin-off increases operational costs in the initial phase due to investments in systems, infrastructure, and human resources. Nevertheless, in the long term, the policy has the potential to improve operational efficiency, financial transparency, institutional independence, and overall financial performance. Therefore, the successful implementation of the spin-off depends on regulatory readiness, managerial capability, and financial resilience